Biomechanical impacts of 3D arch-support insoles on countermovement jumps: a statistical parametric mapping analysis - Shi, Qiu-qiong; Yick, Kit-lun; Huang, Rui-feng; Li, Chu-hao; Wu, Jin long (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveDespite the widespread use of arch-support insoles in sports, their time-dependent biomechanical effects on dynamic movements like countermovement jumps (CMJs) remain poorly understood. This study investigated the biomechanical impacts of three-dimensional (3D) arch-support insoles with varying degrees of stiffness on CMJs by using a statistical parametric mapping (SPM) analysis.DesignRandomized crossover study.MethodTwelve active male university students tested three different polyurethane 3D arch-support insoles (i.e., soft, semi-rigid, and rigid insoles). A total of 16 reflective markers were placed on the lower limbs of the participants according to the Vicon Plug-in Gait marker set protocols. The lower limb kinematics and kinetics were captured by using two synchronized force plates and an eight-camera motion analysis system. SPM was used to statistically compare the biomechanical changes across the different 3D insoles during six continuous key phases of CMJs.ResultsWith the 3D arch-support insoles donned, supra-threshold clusters of the ankle kinematics in the sagittal and frontal planes exceeded the critical thresholds during propulsion-flight (p = 0.022) and the landing (p = 0.033). Ankle moment in the transverse direction exceeded the critical threshold of 6.46 during propulsion (p = 0.038) and landing (p < 0.001). The critical threshold of 6.555 was exceeded for propulsion (p = 0.050) and landing (p < 0.001) with supra-threshold clusters for the force in the frontal plane of the knee. Ankle force in the transverse direction showed that the supra-threshold clusters exceeded the critical threshold during weighing-unweighting (p < 0.001), and early landing (p = 0.007).ConclusionRigid and semi-rigid 3D arch-support insoles significantly altered the biomechanics of the ankle joint, primarily in the frontal and transverse planes during propulsion-flight, and the landing phases. The rigid 3D insole most effectively enhanced ankle joint stability, which is crucial for maintaining balance and preventing injuries. SPM provided a time-dependent analysis of the biomechanical impacts during CMJ.